Education and science: current trends - Bodrov A. G., Nikishina A. A., Novikov I. A., Novikov A. P., Surkova G. V., Petrova D. D., Samostroenko G. M., Shatokhina O. V., Cherkashin I. S., Kapustina N. V., Rustamova I. T., Savenkov D. L., Veselova N. I., Grigorian S. S., Milioshina N. A., Firsova I. A., Chibilyova V. P., Chibiliov A. A., Sagitova V. R., Borovkova V. A., Borovkova V. A., Shevtsov V. V., Efremov A. Y., Diakieva B. B., Averianova E. V., Belonovskaia I. D., Sorokina O. A., Rakhimova O. N., Emelianova E. V., Chereshneva I. E., Kokhanova L. A., Golovko S. B., Khokhrina I. S., Khachev M. M., Temmoeva S. A., Cherkasova O. A., Zakirov R. S., Belousova rimma iurevna R. I., Novoselova A. N., Podoplelova N. M., Danilchenko S. L., Boldyrikhina V. N. (Education and science: current trends, 2018)
the monograph for the first time formulated and described the spiral technology of research and modeling of natural intelligence with three-step turns. Currently, only the first two steps of the first round of spiral technology are widely known. The need for this technology is dictated by the inability to know the natural intelligence, dissecting it or scanning by any radiation. The technology allows us to switch to high-performance systematic work instead of discussions about the nature of artificial and natural intelligence, as well as instead of the dreamy expectation of mysterious heuristics to address issues raised in the creation of artificial intelligence. The basis of the theory in the creation of a new technology is the result of the search for a constructive character in the interpretation of the concept of natural intelligence, that is, the interpretation of the triune nature of natural intelligence. The primary purpose of research on the subject of the monograph, the authors adopted the formulation and description of the theoretical basis of solving the problems of knowledge representation in computer systems. The creation of a theoretical basis becomes possible only with the realization of the triune nature of natural intelligence. The theoretical basis corresponds to the natural science positions in the study and modeling of the epistemological model (objectively isolated part, the unity with the other two parts of the natural intelligence component). The theoretical basis is in demand for obtaining knowledge models in computer systems, allocation on a set of these models of classes, and thus, for the formation of technical requirements in the work on the creation of new shells of knowledge-based systems that implement knowledge models of new classes. In the works focused on achievement of the declared purpose, and in the monograph it is convincingly shown that the whole layer of already executed large-scale works on formation of classes of models of knowledge in computer systems was not based on natural science positions, and for this reason results of already performed works are not demanded at creation of new systems based on knowledge. A significant part of the monograph contains a description of the historical aspect of the works on the stated topic. The consideration of the historical aspect allowed us to see the subjective reasons why the simple to understand and use spiral technology with three-step turns (the theoretical basis for solving the problems of knowledge representation in computer systems) for so long from the moment of formation and recognition of the scientific direction «artificial intelligence» remained undetected and not described for use in research and modeling of natural intelligence in the creation of artificial intelligence. The description of the historical aspect shows the forced reorientation of works on the topic from purely practical (not provided with a theoretical basis) to purely theoretical (not accompanied by works on the modernization of a software product and its implementation in real production). It is also noted that the return to the rails of highly profitable practical work is possible and appropriate. And, accordingly, recommendations for reorientation of works on the topic on the rails of practical and highly profitable are given.
Keywords: искусственный интеллект; представление знаний в компьютерных системах; классы моделей знаний; knowledge representation in computer systems; classes of knowledge models; artificial intelligence; modeling of natural intelligence; creation of shells of knowledge-based systems; моделирование естественного интеллект; создание основанных на знаниях оболочек систем